Design and Analysis of Online Shop Display Based on Augmented Reality Technology - Saputra, Adi Panca; Budiarta, Komang; Rinas, Wayan (International Journal of Engineering and Emerging Technology; Vol 1 No 1 (2016): July - December)
With the rapid development of e-commerce, more and more products sold over the internet. But online shopping site is still using the traditional 2D animation, images and text information for displaying their products that cannot meet the needs of today's consumers to understand the product. Based on an analysis of display technology e-commerce systems that exist, this paper studied the virtual product display technology based on augmented reality and is valid for online display prototype system for watches. This technology can be used in e-commerce as well. This can reinforce the traditional view, improve the consumer shopping experience and increase consumer desire to buy something, and eventually bring good benefits to the customer.